Pemanfaatan Pati Ubi Jalar (Ipomoea batatas L.) Sebagai Bahan Baku Pembuatan Plastik Biodegradable dengan Penambahan Plasticizer Gliserol - Vinezia Sri Wahyuni; Sri Benti Etika (Departemen Kimia FMIPA UNP, 2022)
Research on the utilization of sweet potato starch (Ipomoea batatas L) as a raw material for making plastics biodegradable with the addition of plasticizer glycerol has been successfully carried out. The purpose of this study was to determine the effect of adding plasticizer glycerol to the mechanical, physical, biodegradable and structural properties of plastic biodegradable from sweet potato starch. This research is an experimental study by varying the amount of glycerol as much as 0 mL, 0.2 mL, 0.4 mL, 0.6 mL, 0.8 mL, and 1 mL. The process of making plastic is carried out at a temperature of 70 oC for 15 minutes. Based on the research that has been done, the results show that the more glycerol added, the greater the percentage value of water content and the ability of the plastic to be degraded. The maximum tensile strength was obtained from the addition of 0.4 mL of glycerol of 8.91 Mpa. Plastic biodegradable with the addition of 1 mL of glycerol degraded as much as 83.812% for 6 days. The FTIR spectra showed almost the same peaks between plastics without the addition of glycerol and with the addition of glycerol, the functional groups contained in the plastics included CH, OH, N-H, and C-O.